2018
DOI: 10.3390/en11040905
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Off-Grid Optimal Hybrid Energy System for Rural Electrification of Tanzania Using a Closed Loop Cooled Solar System

Abstract: A large proportion of the world's populations live in developing countries. Rural areas in many of these countries are isolated geographically from grid connections and they have a very low rate of electrification. The uninterrupted power supply (UPS) in these regions is a considerable challenge. The use of renewable energy resources (RER) in an off-grid hybrid energy system can be a pathway to solving this problem. Tanzania has a very low electrification rate (rural 16.9%, urban 65.3%). This paper discussed, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 27 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…In their exploration, the authors identified, among other renewable energy technologies, the feasibility of generating electricity through biogas energy-based hybrid systems for rural areas, particularly in sites with a substantial amount of livestock. In this review, the authors mentioned the need for further investigation for harnessing effectively the potential of hybrid technology for commercial use [53]. Through simulation, Paul et al investigated the possibility of integrating a solar-PV/battery system with DG.…”
Section: The Survey Of Using Ress For Rural Electrificationmentioning
confidence: 99%
“…In their exploration, the authors identified, among other renewable energy technologies, the feasibility of generating electricity through biogas energy-based hybrid systems for rural areas, particularly in sites with a substantial amount of livestock. In this review, the authors mentioned the need for further investigation for harnessing effectively the potential of hybrid technology for commercial use [53]. Through simulation, Paul et al investigated the possibility of integrating a solar-PV/battery system with DG.…”
Section: The Survey Of Using Ress For Rural Electrificationmentioning
confidence: 99%
“…Ponsich et al (2022) have developed an optimization model to determine the optimal size of PV/WTs/BES stand-alone hybrid system that used to supply two remote areas. Khan et al (2018) have investigated the feasibility of stand-alone hybrid system includes PV/WTs/BES by using HOMER to optimize the proposed system. Fioriti et al (2022) have developed a making decision framework based on particle swarm optimization to optimize PV/BES stand-alone hybrid system.…”
Section: Introductionmentioning
confidence: 99%
“…The shrinking of fossil fuel reserves and increasing prices have led to the search for non-pollutant, cheap, environment-friendly, and sustainable energy alternatives for replacement (Neves et al, 2018;Rafindadi et al, 2018;Ren et al, 2018;Rezk et al, 2019). Consequently, more attention by experts was paid on renewable energy sources (RESs) because they are cheaper, environment-friendly, easily accessible, and more importantly sustainable when compared to fossil fuels (Diab et al, 2015;Gomaa et al, 2018;Khan et al, 2018;Tahir et al, 2021). That is why, managements are urged to modify their interests and directions to RESs such as solar energy, wind energy, geothermal heat, hydropower, tidal energy, and biofuels (Ghenai and Janajreh, 2016;Mohamed et al, 2017;Abdelkareem et al, 2018;Abdelkareem et al, 2019;Inayat et al, 2019;Sayed et al, 2019).…”
Section: Introductionmentioning
confidence: 99%